REVEALING THE MEANING OF "NAQOTU" IN THE STORY OF PROPHET SHALEH (APPLICATION OF FERDINAD DE SAUSSURE'S SEMIOTICS TO Q.S AL-A'RAF VERSE 73) - Muhammad Yusuf Darasyiddin A Safa'a; Willy Mulyana; Arman; Erba Putra Diansyah; Muhamad Ifan Permana; Muhammad Syaifullah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This article expands Ferdinand de Saussure’s semiotic studies on Qur’anic verses by analyzing the word "naqotu" in the story of Prophet Saleh to reveal its symbolism and significance. The central question is how to apply Saussure’s semiotic theory to Qur’an, Surah Al-A’raf verse 3. Using library research and analysis of interpretive texts and semiotic literature, the findings indicate that, according to Saussure’s theory, "naqotu" (female camel) as a signifier is distinguished by its physical traits from male camels. As a signified, this she-camel symbolizes a miracle demonstrating God’s power, exceeding the Thamud's skills in stone carving and architecture, and represents wealth and prosperity in Arab culture. This research enriches Qur’anic studies and semiotics by offering new interpretations of symbolism in the story of Prophet Saleh.